Rudey's Windy Christmas - Baugh, Helen and Mantle, Ben (HarperCollins, 2014)
A hilarious story full of noises and naughtiness. A sure-fire Christmas cracker of a book! Oh, dearie me! said Rudy. Now I've done a windy pop! This is a bit embarrassing. I'll do my best to stop. Rudy has eaten too many sprouts and the explosive effect is smelt all around the world as he Santa delivery presents on Christmas Eve... The other reindeer have laughed so much, they're out of puff. How ever will they get the sleigh back home? A naughty, noisy, rip-roaring story, full of hilarious phrases that children will love!
Keywords: Christmas & Advent; Holidays & Celebrations; Juvenile Fiction